Energy in transition, 1985-2010 : (W. H. Freeman, 1980)
The energy problem now faced by the United States began to be recognized 10 years or more ago. Still, the occasional symptoms 9the oil embargo of 1973, the natural gas shortage of 1976-1977, and the gasoline lines of the summer of 1979) are frequently mistaken for the problem itself. As each symptom is relieved, the public sense of crisis fades. The seeds of future crisis, however, remain...